2020
DOI: 10.1111/ijcp.13511
|View full text |Cite
|
Sign up to set email alerts
|

Necessity and concerns about lipid‐lowering medical treatments and risk factors for non‐adherence: A cross‐sectional study in Palestine

Abstract: Aims Strong evidence indicates that drugs reduce blood lipids and improve cardiovascular end‐points, leading to their wide usage. However, the success of these drugs can be affected by poor patient's adherence to prescribed medication. This study aimed to evaluate medication adherence in patients with dyslipidaemia in association with patient beliefs about medicines. Methods The study was conducted from January 2019 to July 2019 at the middle governmental primary healthcare clinics in Ramallah and Bethlehem ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Non-adherence was considered if statins and/or ezetimibe were stopped or dosage was decreased Increased non-adherence: peripheral artery disease, atrial fibrillation, coronary artery bypass surgery Decreased non-adherence: taking aspirin, P2Y12 inhibitors or β-blockers (at discharge from cardiovascular event) Bruckert et al (2020) 58 Retrospective observational cohort study The Pharmacoepidemiologic General Research eXtension (PGRx)-acute coronary syndrome (ACS) registry, from cardiology centres (France) 2.695 patients Adherence was measured using the Proportion of Days Covered (PDC). Patients were considered adherent if they had a PDC ≥80% Decreased non-adherence: previous cardiovascular disease event Seaman et al (2020) 59 Retrospective observational study Western Australian Population (Australia) 205.924 patients Medication possession ratio (MPR), with the threshold of adherence defined as 80% Increased non-adherence: younger age, living in more remote areas, not having previous ischemic heart disease, not having previous coronary artery revascularization procedure, not having previous statin use, beneficiary status, not taking cardiovascular medication, higher number of other medications Decreased non-adherence: older age Shakarneh et al (2020) 60 Cross-sectional study, by survey Two middle governmental primary healthcare clinics in the cities of Ramallah and Bethlehem (Palestine) 185 patients Adherence was determined using the 4-item Morisky medication adherence scale (MMAS-4). Total scores were summed (range 0–4), with scores of 0–1 denoting high adherence and 2–4 denoting low adherence Increased non-adherence: low education (illiterate), polypharmacy (> 4), comorbidities, concerns about side effects …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-adherence was considered if statins and/or ezetimibe were stopped or dosage was decreased Increased non-adherence: peripheral artery disease, atrial fibrillation, coronary artery bypass surgery Decreased non-adherence: taking aspirin, P2Y12 inhibitors or β-blockers (at discharge from cardiovascular event) Bruckert et al (2020) 58 Retrospective observational cohort study The Pharmacoepidemiologic General Research eXtension (PGRx)-acute coronary syndrome (ACS) registry, from cardiology centres (France) 2.695 patients Adherence was measured using the Proportion of Days Covered (PDC). Patients were considered adherent if they had a PDC ≥80% Decreased non-adherence: previous cardiovascular disease event Seaman et al (2020) 59 Retrospective observational study Western Australian Population (Australia) 205.924 patients Medication possession ratio (MPR), with the threshold of adherence defined as 80% Increased non-adherence: younger age, living in more remote areas, not having previous ischemic heart disease, not having previous coronary artery revascularization procedure, not having previous statin use, beneficiary status, not taking cardiovascular medication, higher number of other medications Decreased non-adherence: older age Shakarneh et al (2020) 60 Cross-sectional study, by survey Two middle governmental primary healthcare clinics in the cities of Ramallah and Bethlehem (Palestine) 185 patients Adherence was determined using the 4-item Morisky medication adherence scale (MMAS-4). Total scores were summed (range 0–4), with scores of 0–1 denoting high adherence and 2–4 denoting low adherence Increased non-adherence: low education (illiterate), polypharmacy (> 4), comorbidities, concerns about side effects …”
Section: Resultsmentioning
confidence: 99%
“… 41 Also, in patients presenting side effects or expressing concerns about them, non-adherence is higher, 14 , 24 , 53 with an associated odds ratio of 2.89. 60 Non-adherence is also worst in patients having a higher duration of lipid-lowering treatment. 19 , 47 On the other hand, several studies have shown that non-adherence is lower in patients taking β-blockers, 55–57 who have approximately less 12% risk of non-adherence 27 , 54 as in patients taking other cardiovascular medications.…”
Section: Resultsmentioning
confidence: 99%